Structuri argumentative în discursul juridic grecesc în epoca atică - Lavinia Ionela Savu (Revista de Istorie și Teorie Literară)
The present study analyzes the peculiarities of the juridical discourse of the “golden era” in ancient Greek culture (the Attic period) during which classic oratory had reached its climax. Both compositional and argumentative structures are analyzed. Our conclusion is that everything we see today in both theory and practice of modern law discourse (as well as in other genres), and everything that has been discovered in modern theories of rhetoric owe their very existence to this Greek model promoted by the orators selected in the Canon of Alexandria. This observation can be validated by looking at both the techniques used in their argumentation and the way the spoken word was being manipulated in the ancient texts that we have analyzed.